2023
DOI: 10.1007/s13555-023-00905-3
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Systemic Therapies for Treatment of Psoriasis in Patients with a History of Treated Solid Tumours: Inference-Based Guidance from a Multidisciplinary Expert Panel

Abstract: Background Patients with treated solid tumours (TSTs) are a highly heterogeneous population at an increased risk for malignancy compared with the general population. When treating psoriasis in patients with a history of TSTs, clinicians are concerned about the immunosuppressive nature of psoriasis therapies, the possibility of augmenting cancer recurrence/progression, and infectious complications. No direct, high-level evidence exists to address these concerns. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“… 29 Methotrexate is not a promoter or inducer of cancer, and is often used as a chemotherapeutic agent for solid organ tumors. 30 Registry data have been reassuring to date, with no increased risk of malignancy seen with low-dose methotrexate exposure in psoriasis patients, regardless of duration of treatment. 23 In a recent Inference-Based Guidance from a Multidisciplinary Expert Panel, Papp et al concluded that in psoriasis patients with a history of solid organ malignancy, methotrexate exposure is unlikely to alter prognosis related to their previous malignancy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 29 Methotrexate is not a promoter or inducer of cancer, and is often used as a chemotherapeutic agent for solid organ tumors. 30 Registry data have been reassuring to date, with no increased risk of malignancy seen with low-dose methotrexate exposure in psoriasis patients, regardless of duration of treatment. 23 In a recent Inference-Based Guidance from a Multidisciplinary Expert Panel, Papp et al concluded that in psoriasis patients with a history of solid organ malignancy, methotrexate exposure is unlikely to alter prognosis related to their previous malignancy.…”
Section: Discussionmentioning
confidence: 98%
“… 23 In a recent Inference-Based Guidance from a Multidisciplinary Expert Panel, Papp et al concluded that in psoriasis patients with a history of solid organ malignancy, methotrexate exposure is unlikely to alter prognosis related to their previous malignancy. 30 Methotrexate was trialed as an alternative treatment for 2 patients. It failed to control disease in 1 patient.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, for patients with a less favorable cancer prognosis, the primary objective shifts to enhancing their quality of life. In such instances, the potential benefits of treating psoriasis may outweigh the theoretical risks associated with cancer progression [64].…”
Section: Is There a Timing?mentioning
confidence: 99%